1996
DOI: 10.1183/09031936.96.09122606
|View full text |Cite
|
Sign up to set email alerts
|

Risk of traffic accidents in patients with sleep-disordered breathing: reduction with nasal CPAP

Abstract: R Ri is sk k o of f t tr ra af ff fi ic c a ac cc ci id de en nt ts s i in n p pa at ti ie en nt ts s w wi it th h s sl le ee ep p--d di is so or rd de er re ed d b br re ea at th h--i in ng g: : r re ed du uc ct ti io on n w wi it th h n na as sa al l C CP PA AP P Fifty nine patients completed the study. The accident rate was significantly decreased from 0.8 per 100,000 km (untreated) to 0.15 per 100,000 km with nCPAP treatment. Variables that were considered to be likely to increase accident risk (sleeping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
15

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 25 publications
5
88
1
15
Order By: Relevance
“…[23][24][25][26][27][28] Only two of these studies included a concurrently assessed control population 23,26 to allow an assessment of the degree of normalization of accident rates in CPAP-treated subjects. These studies reached somewhat different conclusions: one study 26 showed accident rates reduced among CPAP treated patients to the level of controls, while the other 23 observed accident rate reductions in both treated patients and re-evaluated controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] Only two of these studies included a concurrently assessed control population 23,26 to allow an assessment of the degree of normalization of accident rates in CPAP-treated subjects. These studies reached somewhat different conclusions: one study 26 showed accident rates reduced among CPAP treated patients to the level of controls, while the other 23 observed accident rate reductions in both treated patients and re-evaluated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and a recent metaanalysis 16 support that continuous positive airway pressure (CPAP) treatment improves driving simulator performance [17][18][19][20][21][22] and reduces accident risk. 16,[23][24][25][26][27][28] Two studies found that CPAP treatment of OSA patients returned driving simulator performance to the level of healthy control subjects, 17,22 while another clinical observational study reported that CPAP therapy reduced motor vehicle accident rates to the background rate of the general population. 26 However, these studies suffered from several methodological limitations.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Daytime sleepiness may adversely affect daytime performance and consequently, among other sequelae, influence driving performance [2,3]. Studies evaluating subjective (self-reports) or objective (motor vehicle department) records sustain the opinion that OSAHS confers an increased risk for accidents when driving [4,5]. In addition, performance on driving simulator and vigilance tests of varying complexity have been shown impaired in OSAHS patients [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating subjective and objective records indicate that continuous positive airway pressure (CPAP) therapy reduces collision and crash frequency in OSAHS patients [4,8,12]. In addition, successful treatment with CPAP therapy generally results in improvements of simulated driving performance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Data collected from passenger car drivers show that OSA increases vehicular crash rates (6)(7)(8) and off-road deviations in a driving simulator (9). Driving performance (9) and crash risk (10)(11)(12) may improve if affected drivers are identified and treated. These data signal a need for developing screening strategies that find OSA among commercial drivers and assessments to determine whether such strategies are cost-effective.…”
Section: Introductionmentioning
confidence: 99%